An Educational 3D Maze Game for Bulgarian Orthodox Iconography - Bontchev, Boyan; Paneva-Marinova, Desislava; Draganov, Lubomil (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2016)
Thanks to their specific characteristics, educational video games make game-based learning more effective than traditional teaching approaches with regard of students’ motivation, engagement, and learning outcomes. This demonstrator presents an educational 3D maze video game introducing Bulgarian Orthodox iconography. The structure and learning content of the maze game are defined declaratively by applying several contemporary teaching methods and learning scenarios for Orthodox iconographic art study. Next, the game is generated by means of a special software platform for creation of customizable desktop video maze games for education. The demonstrator outlines both the game design and development processes and provides a tour through the generated educational maze rooms and tunnels. It shows how the game can be adapted according player’s achievements, emotions and performance.
Keywords: Video Game; Maze; Iconography; Game-based Learning